Reviews. Issue 1 (1st July 2018) - Sporton, Gregory; Sporton, Gregory; Sporton, Gregory
Life and Fate, adapted for the stage and directed by Lev Dodin, Maly Drama Theatre Company, Theatre Royal, Haymarket, 12 May 2018Life is a Dream, by Kim Brandstrup, Rambert Dance Company, Sadler''s Wells Theatre, London, 26 May 2018New Work/New Music, The Royal Ballet, Royal Opera House, Linbury Theatre, 8 February 2019